Localizing Sustainabl Development Goals In Banyumas: Local Resource Development Strategy to Compete in The Global Market - Linggarwati, Tundjung (Journal of Indonesian Social Sciences and Humanities, 2023)
The aim of this research is to analyze Banyumas Regency government’s efforts to develop local resources to compete in the global market. This effort is part of the 9th SDGs localization strategy related to industry, innovation, and infrastructure. One of the SDGs 9 targets related to local industry is target 9b, namely supporting the development of domestic technology, research, and innovation in developing countries. The author uses qualitative methods by collecting primary and secondary data. The author interviewed several business actors and representatives from the Banyumas Regency Industry and Trade Service (Dinperindag), scientific literature documents, and mass media. The research results show that local governments have attempted to develop small and medium enterprises as a local economic development strategy by considering local markets, needs, and resources. Regional governments participate in helping local entrepreneurs utilize local resources and exports to compete in the global market.